Do the Externalism and the Internalism in the Debate Over Epistemic Justification Have Indeed the Same Subject? - Szalek, Piotr (Acta Philosophica, 2008)
The internalist-externalist debate is one of the major themes in contemporary epistemology. It concerns the third condition of knowledge: justification or some other property that makes true belief knowledge. The aim of this essay is to consider the internalist and externalist positions in order to determine whether or not, when they argue about justification, they are talking about the same things. I will argue that they are talking about the same matter, but from different perspectives. Namely, internalism is trying to give an account of justification from the first person perspective, whereas externalism prefers the third person perspective. Moreover, the internalist-externalist distinction is connected with the standard meaning of the internal as “introspectible by subject”. Yet the ambiguities of the debate are a consequence of the fact that both sides might be a matter of degree with respect to the three dimensions of justification (i.e. grounds for justification, adequacy of grounds, and the relation between belief and its ground). It is possible to be internalist or externalist in one, two or three of the dimensions of justification. In my opinion, this distinction offers us a good way to avoid confusions between partly internalist and partly externalist theories of justification. In order to achieve this goal, I will explain of the two sides of the debate and present arguments in favour of and against them. Finally, I will try to offer some kind of systematic order to the debate according to the tree dimensions of justification.